Emergent Z2 Gauge Theories and Topological Excitations in Rydberg Atom Arrays - Samajdar, Rhine; Joshi, Darshan G.; Teng, Yanting; Sachdev, Subir (Physical review letters, 2023)
Strongly interacting arrays of Rydberg atoms provide versatile platforms for exploring exotic many-body phases and dynamics of correlated quantum systems. Motivated by recent experimental advances, we show that the combination of Rydberg interactions and appropriate lattice geometries naturally leads to emergent Z2 gauge theories endowed with matter fields. Based on this mapping, we describe how Rydberg platforms could realize two distinct classes of topological Z2 quantum spin liquids, which differ in their patterns of translational symmetry fractionalization. Additionally, we also discuss the natures of the fractionalized excitations of these Z2 spin liquid states using both fermionic and bosonic parton theories and illustrate their rich interplay with proximate solid phases.